2013
DOI: 10.22621/cfn.v126i4.1375
|View full text |Cite
|
Sign up to set email alerts
|

Stand-level Attributes of Snowshoe Hare (<em>Lepus americanus</em>) Habitat in a Post-Fire Trembling Aspen (<em>Populus tremuloides</em>) Chronosequence in Central Yukon

Abstract: . Forty stand-level compositional and structural variables were assessed as possible predictors of Snowshoe Hare pellet densities. Multidimensional scaling was used to identify variables (n = 10) that were most strongly related to pellet densities and was followed by multiple regression. Canopy cover of Trembling Aspen <50 cm tall and Western White Spruce ≤1 m tall, and deadfall depth, in combination, were the best estimators of Snowshoe Hare pellet densities among stands in the chronosequence (P <0.001, 64.5%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 42 publications
1
2
0
Order By: Relevance
“…Similar to the findings of this study, hares have been reported to be associated with conifer‐dominated forests in Wyoming (Berg et al ), Wisconsin (Buehler and Keith ), Colorado (Dolbeer and Clark , Ivan et al ), Utah (Dolbeer and Clark ), Alaska (Feierabend and Kielland ), Washington (Lewis et al ), Maine (Litvaitis et al ), and Minnesota (Pietz and Tester ), USA, and the Yukon (Strong and Jung ) and Nova Scotia, Canada (Orr and Dodds ). In general, conifer stands offer dense canopy cover to help hares avoid avian predators.…”
Section: Discussionsupporting
confidence: 86%
“…Similar to the findings of this study, hares have been reported to be associated with conifer‐dominated forests in Wyoming (Berg et al ), Wisconsin (Buehler and Keith ), Colorado (Dolbeer and Clark , Ivan et al ), Utah (Dolbeer and Clark ), Alaska (Feierabend and Kielland ), Washington (Lewis et al ), Maine (Litvaitis et al ), and Minnesota (Pietz and Tester ), USA, and the Yukon (Strong and Jung ) and Nova Scotia, Canada (Orr and Dodds ). In general, conifer stands offer dense canopy cover to help hares avoid avian predators.…”
Section: Discussionsupporting
confidence: 86%
“…In mammals, recolonization is limited when key attributes of the habitat are eliminated ( Lindenmayer et al, 1999 ) and successful reoccupation relies on the recovery of vegetation cover ( Jennings et al, 2016 , Fox, Taylor & Thompson, 2003 ). For example, for the American hare, Lepus americanus , after a wildfire the response of populations has been associated with variations in undergrowth and canopy cover ( Mowat & Slough, 2003 ; Hodges, Mills & Murphy, 2009 ; Hodson, Fortin & Bélanger, 2011 ; Strong & Jung, 2012 ; Cheng, Hodges & Mills, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Among regenerating spruce stands the proportion of hare-browsed spruce was highest in intermediate-aged stands (30-60 years post burn) (Hodson et al, 2011;Olnes et al, 2019). An analysis of birch and aspen stands indicated highest hare densities were in stands approximately ≤ 20 years post burn (Strong & Jung, 2012). Similar research into lynx and hare densities along a fire chronosequence that did not differentiate between canopy species found highest track density in an intermediate aged burn ( 30 years post-fire) (Paragi et al, 1997).…”
Section: Introductionmentioning
confidence: 87%